Interventions - Chomsky, Noam (London, 2007)
At a time when the United States exacts a greater and greater power over the rest of the world, America$1 (Bs leading voice of dissent needs to be heard more than ever. In over thirty timely, accessible and urgent essays, Chomsky cogently examines the burning issues of our post-9/11 world, covering the invasion and occupation of Iraq, the Bush presidency and the Israeli invasion of Lebanon. This is an essential collection, from a vital and authoritative perspective.s